2012
DOI: 10.5433/1679-0359.2012v33n4p1333
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e fixação biológica do nitrogênio em soja cultivada com doses de lodo de esgoto compostado

Abstract: ResumoA utilização de lodo de esgoto é uma prática altamente promissora para o desenvolvimento de sistemas agrícolas sustentáveis. O objetivo deste trabalho foi avaliar doses de lodo de esgoto compostado, com e sem a inoculação do rizóbio, no teor de N foliar, número de nódulos, massa seca de nódulos e da planta no florescimento. O experimento foi conduzido em casa de vegetação do Departamento de Ciência do Solo e Recursos Naturais da Faculdade de Ciências Agronômicas de Botucatu, utilizando como substrato vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 3 publications
0
11
0
5
Order By: Relevance
“…Pavanelli and Araújo (2009) noticed low nodulation of soybean plants in certain soils and attributed that to low fertility levels. In a work with sewage sludge in soybeans, Lobo et al (2012) observed an increase in number and dry matter of nodules due to the increase of the sludge doses up to 20 t ha -1 and after this there was a decrease.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Pavanelli and Araújo (2009) noticed low nodulation of soybean plants in certain soils and attributed that to low fertility levels. In a work with sewage sludge in soybeans, Lobo et al (2012) observed an increase in number and dry matter of nodules due to the increase of the sludge doses up to 20 t ha -1 and after this there was a decrease.…”
Section: Resultsmentioning
confidence: 97%
“…The contrast treatment x control with mineral fertilizer was found significant only for nodules dry matter. Lobo et al (2012) found great number and mass of nodules using organic residue in soybeans and attributed these results to the numerous nutrients present in the sewage sludge, which can increase the activity of soil microorganisms, including rhizobia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lobo et al (2012) estudaram o uso do lodo de esgoto no cultivo da soja nas doses de 0, 10, 20, 30, 40 t ha -1 , juntamente com a inoculação de bactéria fixadora de nitrogênio (Bradyrizobium Japonic), avaliando o teor de N foliar, massa seca de nódulos e número de nódulos da planta no florescimento. O resultado da união entre essas técnicas foi superior à utilização do lodo sozinho.…”
Section: Lodo De Esgoto Na Produção De Alimentosunclassified
“…Investigações acerca da aplicação de lodos de esgotos como fertilizantes têm sido feitas nas últimas décadas para várias culturas e espécies vegetais (Romeiro et al, 2014;Lobo et al, 2012;Nascimento et al, 2004;Lopes et al, 2005;Sampaio, 2010). Entretanto, quando se lida com resíduos domésticos, é importante que cuidados sejam tomados para evitar contaminações do solo, da água (Gonçalves et al, 2000) e, quando for o caso, dos alimentos produzidos.…”
Section: Introductionunclassified